2020
DOI: 10.3390/ijerph17030736
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Teacher Job Satisfaction: The Contribution of Collective Efficacy and Emotions Towards Professional Role

Abstract: Purpose: The purpose of this paper is to explore whether, and to what extent, collective beliefs and emotions towards professional role could predict job satisfaction, above and beyond the role of self-efficacy and emotions towards students. More specifically, we expected job satisfaction to be incrementally predicted by beliefs and emotions related to professional role (collective efficacy and role-related hedonic balance). Design/Methodology/Approach: The analysis was performed through the administration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 73 publications
3
27
0
1
Order By: Relevance
“…As Chen (2019) explained, the love aspect of teacher emotions is related to passion for teaching, and the love aspect of teacher emotions is reflected by their satisfaction with the teaching profession. Thus, this study validates that while positive emotions predict teacher job satisfaction, as supported by other studies (Buonomo et al, 2020;Chen, 2019b;Hagenauer et al, 2015;Ignat & Clipa, 2012;King & Chen, 2019;Nalipay et al, 2019;Rodrigo-Ruiz, 2016), the job satisfaction of teachers also predicts positive teacher emotions, namely, the joy and love dimensions. One of the most remarkable findings of this current study is that teachers' job satisfaction is a predictor of negative teacher emotions of sadness, anger and fear.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As Chen (2019) explained, the love aspect of teacher emotions is related to passion for teaching, and the love aspect of teacher emotions is reflected by their satisfaction with the teaching profession. Thus, this study validates that while positive emotions predict teacher job satisfaction, as supported by other studies (Buonomo et al, 2020;Chen, 2019b;Hagenauer et al, 2015;Ignat & Clipa, 2012;King & Chen, 2019;Nalipay et al, 2019;Rodrigo-Ruiz, 2016), the job satisfaction of teachers also predicts positive teacher emotions, namely, the joy and love dimensions. One of the most remarkable findings of this current study is that teachers' job satisfaction is a predictor of negative teacher emotions of sadness, anger and fear.…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, negative emotions of anger and sadness were not significantly correlated with job satisfaction. In another recent study which focused on teacher emotions and job satisfaction, Buonomo et al (2020) also indicated that teachers were more satisfied with their jobs when they minimized their negative emotions and adopted positive emotions. Notably, Atmaca et al (2000) found that fear as a negative teacher emotion predicted job satisfaction in a positive way, which supports the current findings.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The deep link with the organizational context is specifically relevant for teachers. Several studies showed that school-related variables (e.g., leadership, collective efficacy, school climate) have a role in how teacher perceive and whether they are engaged in their job ( Ware and Kitsantas, 2007 ; Toytok and Kapusuzoglu, 2016 ; Koutouzis and Malliara, 2017 ; Benevene et al, 2019 ; Fiorilli et al, 2019b ; Buonomo et al, 2020b ). Among these variables, school principals’ ethical leadership may sustain teachers’ proneness to acknowledge others’ needs and support them ( Brown and Treviño, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…A few empirical studies investigated the ratio between positive and negative emotions in an educational context. Specifically, teachers’ hedonic balance (computed as the difference between positive and negative emotions) was positively associated with teachers’ self-efficacy, job satisfaction, and student-related positive emotions ( Buonomo et al, 2019 , 2020 ). Research supporting the broaden-and-build theory among teachers also revealed that positive emotions can reduce the negative effects of negative emotions (i.e., undoing effect) ( Gloria et al, 2013 ; Buonomo et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%